Robustness of digital PCR and real‐time PCR against inhibitors in transgene detection for gene doping control in equestrian sports. Issue 10 (21st July 2021) - Tozaki, Teruaki; Ohnuma, Aoi; Kikuchi, Mio; Ishige, Taichiro; Kakoi, Hironaga; Hirota, Kei‐ichi; Kusano, Kanichi; Nagata, Shun‐ichi
Abstract: Gene doping is a threat to fair competition in sports, both human and equestrian. One method of gene doping is to administer exogenous genetic materials, called transgenes, into the bodies of postnatal humans and horses. Polymerase chain reaction (PCR)‐based transgene detection methods such as digital PCR and real‐time PCR have been developed for gene doping testing in humans and horses. However, the significance of PCR inhibitors in gene doping testing has not been well evaluated. In this study, we evaluated the effects of PCR inhibitors on transgene detection using digital PCR and real‐time PCR against gene doping. Digital PCR amplification was significantly inhibited by high concentrations of proteinase K (more than 0.1 μg/μl), ethylenediaminetetraacetic acid (more than 5 nmol/μl), and heparin (more than 0.05 unit/μl) but not by ethanol or genomic DNA. In addition, phenol affected droplet formation in the digital PCR amplification process. Real‐time PCR amplification was inhibited by high concentrations of phenol (more than 1% v/v), proteinase K (more than 0.001 μg/μl), ethylenediaminetetraacetic acid (more than 1 nmol/μl), heparin (more than 0.005 unit/μl), and genomic DNA (more than 51.9 ng/μl) but not by ethanol. Although both PCR systems were inhibited by nearly the same substances, digital PCR was more robust than real‐time PCR against the inhibitors. We believe that our findings are important for the development of better methods for transgene detection and prevention of false negative results in gene doping testing. Abstract : Gene doping undermines fair competition in sports, both human and equestrian. One method of gene doping is the administration of transgenes into the bodies of postnatal humans and horses. Although digital PCR and real‐time PCR systems were inhibited by high concentrations of proteinase K, EDTA, heparin, and genomic DNA in transgene detection for gene doping control, digital PCR was found to be more robust than real‐time PCR against PCR inhibitors.